Memoirs of William Wordsworth, Volume 1 - Wordsworth, Christopher 1807-1885 (Cambridge library collection. Literary studies, 2014)
This two-volume biography of William Wordsworth (1770–1850) was published in 1851 by his nephew, Christopher (1807–85), a scholar who later became bishop of Lincoln. The introductory chapter argues against the presentation of a 'life', or a critical assessment of Wordsworth's works. The poet felt strongly that the life was in the works, and that they should 'plead their own cause before the tribune of Posterity'. Nevertheless, an elucidation of the facts of Wordsworth's life would - precisely because his poems are so personal - help the reader to understand his verse; and to be best understood, it should be studied chronologically, for which a 'biographical commentary' would be essential. Christopher Wordsworth, having agreed to undertake this task, asked his uncle for a 'brief sketch of the most prominent circumstances of his life'; the remainder of Volume 1 takes the biography up to 1810